Comparative engine performance and emission analysis of CNG and gasoline in a retrofitted car engine - Jahirul, M.I.; Masjuki, Haji Hassan; Saidur, Rahman; Kalam, M.A.; Jayed, M.H.; Wazed, M.A. (Elsevier, 2010)
A comparative analysis is being performed of the engine performance and exhaust emission on a gasoline and compressed natural gas (CNG) fueled retrofitted spark ignition car engine. A new 1.6 L, 4-cylinder petrol engine was converted to the computer incorporated bi-fuel system which operated with either gasoline or CNG using an electronically controlled solenoid actuated valve mechanism. The engine brake power, brake specific fuel consumption, brake thermal efficiency, exhaust gas temperature and exhaust emissions (unburnt hydrocarbon, carbon mono-oxide, oxygen and carbon dioxides) were measured over a range of speed variations at 50 and 80 throttle positions through a computer based data acquisition and control system. Comparative analysis of the experimental results showed 19.25 and 10.86 reduction in brake power and 15.96 and 14.68 reduction in brake specific fuel consumption (BSFC) at 50 and 80 throttle positions respectively while the engine was fueled with CNG compared to that with the gasoline. Whereas, the retrofitted engine produced 1.6 higher brake thermal efficiency and 24.21 higher exhaust gas temperature at 80 throttle had produced an average of 40.84 higher NO(x) emission over the speed range of 1500-5500 rpm at 80 throttle. Other emission contents (unburnt HC, CO, O(2) and CO(2)) were significantly lower than those of the gasoline emissions.